Measurement of Inhibin-A, Activin-A, Relaxin and Progesterone Hormones in patients with missed miscarriage - Maitham Yasser Hussein , Raid M. H. Al-Salih , Alaa H. Al- Nasser, (International Journal of Medical Toxicology and Legal Medicine, 2025)
This study aimed to show the effects of Inhibin–A , Activin-A , Relaxin and Progesterone Hormones in the incidence of missed abortion and normal pregnancy cases in women at first trimester of pregnancy in Thi-Qar Province . This study had been performed in the period between ( November 2023 to September 2024) , included (100) blood random samples of missed abortion and normal pregnancy women, all diagnoses by the Ultrasound scan and other ways as clinical diagnoses and the histery of pregnant , Their range ages between(18-40) years. That samples were obtained from attending women to Bint AL-Huda Hospital and some private medical clinics. The selective samples were divided into two groups , the first group represented 50 blood samples from aborted women, while the second group included 50 blood samples from normal pregnancy women as a control group. The blood samples had taken during the period between (1-3)months of pregnancy.The results revealed a significant decrease in the concentration of Inhibin-A , Activin-A and Progesterone hormones (P≤0.05) in the group of aborted women when compared with the control group.Also the results had showed a high a significant in Relaxin concentration in abortion group (P≤0.05) when compared with the control group . This study confirmed an apparent relationship between the decrease concentrations of inhibin-A , activin-A and Progesterone and incidence of the abortion cases , which emphasizes the important role of their hormones in pregnancy continue